(3GdebJQM aj TQM CHjGJ GHf GdaQMs - (3CHhMaU YeQ Hf YHO Gddg GdaGSjs; (3GHf aQM , CMeO Hf aQM Hf CMeO Hf eMeO Hf aQM GddNej GdGTHjdj, TgGH GdOjf CHh GdYHGS,J (B966 (3g` s
(3ChdgG (B:s
(3CeG HYO ajbhd GdYHO GdabjQ Edi Gddg JYGdi YeQ Hf YHOGddg GdaGSj JbjjO cGdTQM ddBjGJ GdeTghQI Hjf Cgd GdMOjK s
(3BNQgG (B:s
(3hgPG BNQ eGfTQg GdMGaX GdSHcj aj WHbGJg dfGXe GdBjGJ s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B194 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B45s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B/ (3ecJHI GdQHGW (B(D 1256) s
Keywords: (3GdMOjK h GdeUWdMs